(3OjhGf GdfGHZI GdPHjGfjs - (3GdfGHZg GdPHjGfj , RjGO Hf eYGhjg Hf VHGH GdPHjGfj GdZWaGfj GdeVQj, CHh GeGegs
(3ChdgG (B:s
(3bGd GdfGHZI GdPHjGfj, hGSeg RjGO Hf YeQh Hf eYGhjI(B: (3Cef Bd ejI QGFM Ce eZJO YLdGf PG RGO hZjQ eRhO s
(3BNQgG (B:s
(3eG cGf aj eYVO ef Mde Nda eNda HjJ GdZfj hehQK GdbOe Je GdOjhGf hGdMeO ddg hMOg, hUdhGJg Ydi SjOfG hehdGfG eMeO hBdg GdWGgQjf s
(3hGfXQ GdLRA GdChd HQbe (B365s
(3TQM GdOjhGf HQbe (B529 (3COHs
(3hQO CjVkG JMJ Qbe (B502(3, (B503(3, (B1303(3, (B1304(3, (B1866(3, (B1867s
(3jdj GdOjhGf oeNJGQGJ dTYQGA oeNJdajfs
(3hGdOjhGf QhGjI eMeO Hf MHjH s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs